Strengthening Critical Thinking in Engineering Students through Mathematics: The Power of Attitudes (2023)
This study aims to strengthen critical thinking in future engineers through mathematics by stimulating their attitudes. To achieve this, a qualitative informative study will be conducted with a characteristic cut and a deductive orientation through the analysis and synthesis of contents from scientific publications specializing in the development of critical thinking. This type of thinking can be strengthened through strategies proposed by the mathematics teacher, allowing an increase in curiosity, eagerness to learn and inquire, and especially promoting and awakening curiosity in students through contexts where mathematics is formally applied in engineering. These strategies should include concrete actions that foster attitudes of critical thinking and a better ability to argue, interpret, and make judgments independently, ultimately acquiring a set of skills, especially in problem-solving. The results show that an engineering student as a critical thinker must have a critical attitude, which is evidenced through dispositions, habits, and character traits, which, when stimulated through mathematics, would contribute to their professional formation.